2009
DOI: 10.1080/07294360902725025
|View full text |Cite
|
Sign up to set email alerts
|

Disciplining writing: the case for multi‐disciplinary writing groups to support writing for publication by higher degree by research candidates in the humanities, arts and social sciences

Abstract: This article addresses multi-disciplinary writing groups in supporting writing for publication for higher degree by research candidates in the Humanities, Arts and Social Sciences. Drawing on focus group discussions with postgraduate research students from the Faculty of Arts at Monash University in Australia who participated in the writing groups, it investigates the participants' perceptions of the multi-disciplinary nature of the groups and some of the benefits of sharing writing with fellow postgraduate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…As Cuthbert et al (2009) found, the mix of fields involved may have contributed to producing a less 'competitive' environment: there is no need to 'prove' academic superiority. Rather, the focus turns to the writing itself and thoroughly explaining and communicating key concepts of our work so that others can understand.…”
Section: Disciplinary Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…As Cuthbert et al (2009) found, the mix of fields involved may have contributed to producing a less 'competitive' environment: there is no need to 'prove' academic superiority. Rather, the focus turns to the writing itself and thoroughly explaining and communicating key concepts of our work so that others can understand.…”
Section: Disciplinary Diversitymentioning
confidence: 99%
“…I wanted to highlight that the program is intended to be specific to the participants' discipline. There are some persuasive arguments for multi-disciplinary writing groups (see Cuthbert et al 2009, andFerguson 2009, for example), and for multi-disciplinary groups that share broadly similar methodological approaches (Bastalich 2011). However, initially I was under the mistaken impression that the advantage of group members working within the same discipline would be that participants were familiar with at least some of the jargon and specialised knowledge required to understand each others' writing, and that this would develop a growing awareness of the expected conventions of the disciplinary culture.…”
Section: Original Rationale For Establishing the Phew Group: The Acadmentioning
confidence: 99%
“…This has included calls for giving greater pedagogic attention to writing for doctoral students, including the role of co-authorship (Kamler, 2008), as well as drawing attention to the ways in which postgraduates develop a sense of identity as writers (Cameron, Nairn, & Higgins, 2009). Much of the literature about writing skills focuses on the benefits of using seminars and workshops to develop the writing skills of doctoral students (Aitchison, 2009;Burgoine, Hopkins, Rech, & Zapata, 2011;Cuthbert & Spark, 2008;Cuthbert, Spark, & Burke, 2009;Delyser, 2003;Ferguson, 2009). Learning more about academic writing skills, sharing experiences of (and struggles with) writing, gaining confidence as an author, and developing a more positive approach to writing are just some of the benefits that are demonstrated in this work.…”
Section: Developing Writing Skillsmentioning
confidence: 99%
“…Multidisciplinary groups can add to discipline-based doctoral education by providing breadth in students' development; in this sense it complements rather than compromises disciplinary education (Cuthbert, Spark, & Burke, 2009).…”
Section: The Case For Generic Writing Advicementioning
confidence: 99%
“…In much of the research on generic thesis writing programmes, groups have been initiated by the institution, according to a more or less structured format, and have been strongly guided by a staff member (Aitchison, 2003;Cuthbert et al, 2009;Ferguson, 2009;Larcombe, McCosker, & O'Loughlin, 2007). Aitchison (2003) defends such an approach when she states that 'the role of the facilitator is crucial in this small group approach as students must actively and sensitively participate as developing writers as well as learn how to critically appraise the work of others' (p. 97).…”
Section: The Case For Generic Writing Advicementioning
confidence: 99%